Concentration of biologically active polyamines in meat and liver of sheep and lambs after slaughter and their changes in mutton during storage and cooking - Dadáková, Eva; Pelikánová, Tamara; Kalač, Pavel (Meat science, 2011)
Putrescine (PUT), spermidine (SPD) and spermine (SPM) concentrations using a UPLC method, in chilled mutton, lamb and livers 24 h after slaughter were determined. PUT concentrations were quantifiable only in some samples. Mean SPD concentrations were 4-6, 13.5 and 16.8 mg kg-1 in the meats, sheep and lamb livers, respectively. The respective SPM concentrations were 17-25, 128 and 79 mg kg-1. SPD and SPM losses of about one fifth and half of the initial level, respectively, were apparent in mutton loins stored at -18°C for 6 months. Significant losses of SPD and SPM were found in mutton loins stored aerobically, vacuum-packaged or in a modified atmosphere at +2°C. Boiling and stewing of mutton legs caused SPD and SPM losses of about 40% and roasting of about 60% of the initial content.
Keywords: Liver; Sheep; Animals; Cooking; Meat; vaření; ovce; játra; Food Handling; maso; Polyamines; manipulace s potravinami; polyaminy; zvířata